Rapidex Self Letter Drafting Course
This companion guide-book is intended as a concise, practical guide that teaches you how to draft imaginative, forceful, response-producing letters. It also helps you to handle general complaints and keep your social and business contacts smooth and pleasant. All you have to do is to pick up ready-made sentences and arrange according to your requirement. Ideally suited for all occasions and requirements, this thoroughly revised and enlarged edition is compiled by experts. It teaches you hands-on applications of fundamental principles and techniques to create excellent drafts. The book covers almost every topic under the sun